Fluorescent microsphere immunochromatographic assays for detecting bone alkaline phosphatase based on biolayer interferometry-selected antibody. Issue 52 (28th June 2017) - Liu, Miao; Zeng, Li-Feng; Yang, Ya-Jie; Hu, Li-Ming; Lai, Wei-Hua
Abstract : A convenient, reliable, highly sensitive, and competitive fluorescent microsphere-lateral flow immunochromatographic assay (FM-LFIA) was developed for the quantitative detection of BAP for the first time. Abstract : Bone alkaline phosphatase (BAP) is commonly used as a clinical marker for diagnosing and monitoring overall metabolic bone disease. In this study, a convenient, reliable, highly sensitive, and competitive fluorescent microsphere-lateral flow immunochromatographic assay (FM-LFIA) was developed for the quantitative detection of BAP for the first time. The antibody (ab17272) with the minimum equilibrium dissociation constant ( K D, K D = 1.503 × 10 −8 M) used in FM-LFIA was selected by the biolayer interferometry system. Various parameters that influence the FM-LFIA were optimized. Under the optimized conditions, the limit of detection for BAP was 0.1 ng mL −1 within 15 min with a good linear range of 0.1 ng mL −1 to 250.0 ng mL −1 . The average recoveries for intra- and inter-assays ranged from 98.6% to 103.8% and 92.4% to 111.5% with corresponding CVs of 6.7% to 8.5% and 4.6% to 9.3%, respectively. The test strips showed satisfactory stability through an accelerated aging test at 60 °C for 6 days. Owing to its high sensitivity and simplicity, FM-LFIA can be easily used to rapidly detect BAP.